59 Pace and ablate for poorly controlled AF – how does it affect heart failure metrics?. (16th October 2019) - Esmonde, S; Soong, C-N; Kerr, B; McKeag, N; McCann, C; Cromie, N; Chew, E-W
Abstract : Background: Atrioventricular nodal ablation (AVNA) is indicated in drug-refractory atrial fibrillation (AF)[1], and has been shown to improve cardiac resynchronization therapy (CRT) efficacy in this cohort[2]. There is concern over the potentially detrimental effect of long-term right ventricular (RV) apical pacing on heart failure metrics[3], but there is no consensus as to which pacing approach should be undertaken initially, especially when left ventricular ejection fraction (LVEF) is normal[4–6]. This observational study aims to inform as to the effect of AVNA on heart failure metrics and CRT efficacy. Methods: Patients were identified retrospectively from records of patients undergoing AVNA for drug-refractory AF in a single centre over a 3-year period (January 2016 – December 2018). Baseline and post-procedure echocardiographic measurements of LVEF and NT-proBNP levels were obtained from electronic records. Those with a CRT device in-situ had pre- and post-AVNA biventricular pacing percentages recorded electronically, successful threshold defined as ≥95%. For initial analysis, patients were categorised as having impaired (<55%) or normal (≥55%) LVEF. Data represents mean ± SEM and were analysed using paired student t-test. Results: 106 patients (mean age 72.1 years, 55% female) underwent AVNA during this time period. 18/106 (17.0%) had a normal LVEF at baseline. CRT was performed in 46/106 (43.4%), and 94.1% of this group had an impaired LVEF pre-AVNA compared with 6.9% with a normal LVEF pre-AVNA. Post-AVNA, LVEF significantly increased in patients with already impaired LVEF (31.4±3.2% to 41.2±3.8%, P<0.05) compared to those with normal LVEF (53.0±9.3% to 60.0±3.4%). NT-proBNP levels did not significantly change in either group. LVEF also significantly increased in patients post-AVNA who had a CRT device in-situ (30.1±3.1% to 49.8±6.5%, p<0.05) compared with those treated with RV pacing only (49.9±6.9% to 49.8±6.5%). In addition, NT-proBNP levels significantly decreased in patients who underwent CRT (3175±431.9 pg/ml to 1482.1±176.8 pg/ml, p<0.05) compared to those treated with RV pacing only (4135.1±911.6 pg/ml to 2722.5±671.5 pg/ml). The number of patients receiving successful biventricular pacing rose from 11/46 (23.9%) to 38/44 (86.4% (2 patients lost to follow-up)) post-AVNA. Conclusion: AVNA was associated with a significant improvement in heart failure metrics in patients with an already impaired LVEF, and in those with a CRT device in-situ, we suggest this is through improved rate control and biventricular pacing percentage. A pace and ablate strategy was not associated with worsening in heart failure metrics in patients with a normal LVEF at baseline, suggesting up-front CRT in this group is not justifiable. Larger randomized controlled trials would be helpful to confirm these findings.